2022
DOI: 10.1007/s10853-022-06877-7
|View full text |Cite
|
Sign up to set email alerts
|

Highly ordered pure and indium-incorporated MCM-41 mesoporous adsorbents: synthesis, characterization and evaluation for dye removal

Abstract: Highly ordered pure MCM-41 and In-MCM-41 mesoporous adsorbents (with Si/In = 95 (IM0.05) and Si/In = 90 (IM0.1)) were synthesized using the hydrothermal-assisted method. The structural, morphological and texture characteristics were investigated by XRD, N2 adsorption–desorption, SEM-EDX, TEM, diffuse reflectance (DR) and FTIR. The broadening XRD diffraction peaks as well as the shifts to higher and lower 2-theta in IM0.05 and IM0.1, respectively, confirmed the incorporation of indium atoms in the MCM-41 struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 86 publications
3
12
0
Order By: Relevance
“…As a general trend, there is a broadening of the diffraction peaks accompanied by shifts to higher or lower 2theta degrees, accompanied by shifts to higher or lower 2theta degrees. In this broadening, the loss of some characteristic peaks or the decrease of their intensity is a distinctive indication of the incorporation of metals into the silica structure [44] . This could be consistent with the values reported by Casas‐ Orozco et al.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…As a general trend, there is a broadening of the diffraction peaks accompanied by shifts to higher or lower 2theta degrees, accompanied by shifts to higher or lower 2theta degrees. In this broadening, the loss of some characteristic peaks or the decrease of their intensity is a distinctive indication of the incorporation of metals into the silica structure [44] . This could be consistent with the values reported by Casas‐ Orozco et al.…”
Section: Resultssupporting
confidence: 92%
“…In this broadening, the loss of some characteristic peaks or the decrease of their intensity is a distinctive indication of the incorporation of metals into the silica structure. [44] This could be consistent with the values reported by Casas-Orozco et al. [45] , and Gonzalez-Vargas et al, [46] who demonstrated that high dispersion of metal oxide in the silica matrix, results in the reduction of its bandgap.…”
Section: Bandgap Energy Determination Of Mcm-41@ag Nanocompositesupporting
confidence: 90%
“…The diffractogram of pure MCM-41 contain a strong peak ranging from 2ϴ= 2-3̊ corresponding to 100 planes with 2 weaker reflections at 4.4 (110) and 4.9 (200) planes, respectively. Appearance of these peaks confirmed the synthesis of highly ordered hexagonal mesostructure [45].After modification with organic moieties, the sharp reflection of 100 plane converted into broad peak with lower intensity meanwhile the 110 and 200 peaks to be weakened and consequently disappeared, indicating reduction in the long range-ordering mesostructure of MCM-41 channel [46]. Moreover, the existence of characteristic diffraction 100 in all the samples prove that MCM-41 still hold the hexagonal mesoporous structure even after grafting with metal complex.…”
Section: 12powder Xrd Studiesmentioning
confidence: 71%
“…Schiff base ligand (E)-2-((pyridin-4-ylmethylene)amino)phenol (PAL) was synthesized with the help of literature [44] and characterized with the help of NMR spectroscopy ( 1 H and 13 C)…”
Section: Synthesis Of Schiff Base Ligand (Pal)mentioning
confidence: 99%
“…This successful surface dispersion aligns with the loading process and hints at a potential interaction between the Ag NPs and the MCM-41 surface. 49…”
Section: Resultsmentioning
confidence: 99%